A new macro-element model encapsulating the dynamic moment-rotation behaviour of raft foundations - Heron, Charles; Haigh, S.K.; Madabhushi, S.P.G. (Thomas Telford ICE Publishing, 2015)
The interaction of shallow foundations with the underlying soil during dynamic loading can have both positive and negative effects on the behaviour of the superstructure. Although the negative impacts are generally considered within design codes, seldom is design performed in such a way as to maximise the potential beneficial characteristics. This is, in part, due to the complexity of modelling the soil–structure interaction. Using the data from dynamic centrifuge testing of raft foundations on dry sand, a simple moment–rotation macro-element model has been developed, which has been calibrated and validated against the experimental data. For the prototype tested, the model is capable of accurately predicting the underlying moment–rotation backbone shape and energy dissipation during cyclic loading. Utilising this model within a finite-element model of the structure could potentially allow a coupled analysis of the full soil–foundation–structure system's seismic response in a simplified manner compared to other methods proposed in literature. This permits the beneficial soil–structure interaction characteristics, such as the dissipation of seismic energy, to be reliably included in the design process, resulting in more efficient, cost-effective and safe designs. In this paper the derivation of the model is presented, including details of the calibration process. In addition, an appraisal of the likely resultant error of the model prediction is presented and visual examples of how well the model mimics the experimental data are provided.